Utilisation of Supercritical Critical Fluids in Adsorption Process: A Comprehensive Review - Murtala NAMAKKA; Abdulhamid S. ILIYASU (FUDMA Journal of Engineering and Technology, 2026)
Conventional separation and purification processes in industries like pharmaceuticals and environmental remediation often face significant challenges, including high energy consumption, the use of large amounts of hazardous organic solvents, and limited efficiency in extracting or adsorbing target compounds. This review comprehensively examines the utilization of supercritical fluids SCFs in adsorption processes, highlighting their unique physicochemical properties such as tuneable density, low viscosity, and high diffusivity that bridge the gap between liquid and gas phases. The discussion covers fundamental adsorption mechanisms, thermodynamic principles, and the role of adsorption isotherms in supercritical conditions. Key applications in pharmaceuticals (e.g., drug encapsulation and controlled release), environmental remediation and separation processes are detailed. The review also addresses advanced adsorbent materials, including porous and nanostructured adsorbents, and their surface modification for enhanced performance. Furthermore, mass transfer mechanisms, kinetic modelling, and process integration such as supercritical fluid-assisted adsorption, extraction, and desorption are analysed. Despite significant advantages in efficiency, selectivity, and sustainability, challenges related to process optimization, material compatibility, and scalability remain. The review concludes with prospects, emphasizing the potential of SCFs in advancing green technologies and industrial applications through continued research and interdisciplinary innovation.